Cryo-EM advances in GPCR structure determination - Shihoya, Wataru; Iwama, Aika; Sano, Fumiya K; Nureki, Osamu (Journal of biochemistry (Tokyo), 2024)
G-protein-coupled receptors (GPCRs) constitute a prominent superfamily in humans, and are categorized into six classes (A through F) that play indispensable roles in cellular communication and therapeutics. Nonetheless, their structural comprehension has been limited by challenges in high-resolution data acquisition. This review highlights the transformative impact of cryogenic electron microscopy (cryo-EM) in the structural determinations of GPCR-G-protein complexes. Specific technologies such as nanobodies and mini-G-proteins stabilize complexes and facilitate structural determination. We discuss the structural alterations upon receptor activation in different GPCR classes, revealing their diverse mechanisms. These cryo-EM structures provide a robust foundation for comprehending GPCR function and pave the way for future breakthroughs in drug discovery and therapeutic targeting.